2023
DOI: 10.3389/fnins.2023.1146946
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture treatment for post-stroke depression: Intestinal microbiota and its role

Abstract: Stroke-induced depression is a common complication and an important risk factor for disability. Besides psychiatric symptoms, depressed patients may also exhibit a variety of gastrointestinal symptoms, and even take gastrointestinal symptoms as the primary reason for medical treatment. It is well documented that stress may disrupt the balance of the gut microbiome in patients suffering from post-stroke depression (PSD), and that disruption of the gut microbiome is closely related to the severity of the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 180 publications
0
9
0
Order By: Relevance
“…to digestive system disorders including changes in intestinal motility, damaged mucosal barriers, and dysbiosis (Jiang et al, 2023). Gut microbiota produces various signaling molecules and metabolites, such as neurotransmitters, hormones, and short-chain fatty acids (SCFAs) (Panther et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to digestive system disorders including changes in intestinal motility, damaged mucosal barriers, and dysbiosis (Jiang et al, 2023). Gut microbiota produces various signaling molecules and metabolites, such as neurotransmitters, hormones, and short-chain fatty acids (SCFAs) (Panther et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory mediators disrupt gut barrier function and microbial balance, further exacerbating the inflammatory state, impacting stroke recovery, and promoting the development of PSD. In addition, PSD is also influenced by both brain ischemic injury and chronic stress, which interfere with normal gut function, leading to digestive system disorders including changes in intestinal motility, damaged mucosal barriers, and dysbiosis (Jiang et al., 2023 ). Gut microbiota produces various signaling molecules and metabolites, such as neurotransmitters, hormones, and short‐chain fatty acids (SCFAs) (Panther et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is theorized that acupuncture helps balance the gut microbiota, thereby improving the intestinal barrier and immune system. This balance could be a key factor in acupuncture’s impact on the gut-brain axis [ 50 ]. In contrast to antibiotics, which can have negative effects on gut and mental health, acupuncture is suggested to increase microbial alpha diversity [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, how much of the benefit of exercise on the brains of AD patients comes from the reductions in LPS remains to be further confirmed. In addition, LPS is a major component of the cell walls of Gram-negative bacteria in intestinal microbes, and maintaining the ecological balance of intestinal microbes can reduce the production of LPS [ 47 , 48 ]. Our previous study found that treadmill exercise enriched intestinal microbes, reduced harmful bacteria, and protected the blood–brain barrier in AD mice [ 20 ], suggesting that treadmill exercise may regulate various aspects of the microbial–gut–liver–brain axis to reduce the entry of LPS into the brain, but the magnitude of the effect of exercise on these aspects and the causal relationship between these aspects remain to be confirmed by further studies.…”
Section: Discussionmentioning
confidence: 99%